Reduced cortical thickness in first episode schizophrenia. - Schultz CC; Koch K; Wagner G; Roebel M; Schachtzabel C; Gaser C; Nenadic I; Reichenbach JR; Sauer H; Schlösser RG; Schultz, C Christoph; Koch, Kathrin; et al. (Schizophrenia Research, 2010)
Objective: Previous morphometric studies are suggesting altered cortical thickness mainly in prefronto-temporal regions in first episode schizophrenia. In an extension of these earlier studies, we used an entire cortex vertex-wise approach and an automated clustering for the detection and exact quantification of cortical thickness alterations in first episode schizophrenia.Methods: A group of 54 patients with first episode schizophrenia according to DSM-IV and 54 age and gender matched healthy control subjects were included. All participants underwent high-resolution T1-weighted MRI scans on a 1.5 T scanner. Cortical thickness was estimated as the distance between the gray-white matter border and the pial surface using an automated computerized algorithm (Freesurfer Software). Statistical cortical maps were created to estimate differences of cortical thickness between groups based on this entire cortex analysis.Results: Significant cortical thinning was observed in first episode schizophrenia patients relative to controls in a number of cortical areas including the dorsolateral and frontopolar cortices, the anterior cingulate cortex, a ventrolateral-orbitofrontal cluster, as well as the superior temporal cortices and superior parietal lobe. Cortical thinning within these regions was on average 4.4-5.7% with strongest reductions in orbitofrontal regions (7.1%).Conclusions: The present findings suggest widespread reduction of cortical thickness, mostly in heteromodal cortices of fronto-temporal networks to be present at an early stage of schizophrenia. Taken together, the present morphometric data in first episode schizophrenia provide further evidence for potential neurodevelopmental deficits and disruption of cortical maturation in this disorder.